Manoel Augusto dos Santos: sua atuação no cenário pedagógico do piano em Recife - Albuquerque, Janete Florencio de Queiroz (2015)
This study aimed to investigate the role of the teacher and pianist Manuel Augusto dos Santos in the piano pedagogical scenario, according to the cultural context of the city of Recife in the twentieth century. The research approach was qualitative, historical, educational, and musical in nature in which many contextual and temporal elements intertwine with subjective speeches and with the involvement of the researcher with the subject researched. The "practice of biography", a term which refers to micro-history, was chosen as the main theoretical framework to verify the relationship with the subject and its proper questioning about the historical issues. The "psycho-technical school" was the theoretical reference for the pedagogical issues of teaching and learning piano regarding the teaching practice carried out by Manuel Augusto. This school advocates complete freedom in the use of all parts of the pianistic apparatus where the role of the mind is essential. The first part investigated was the musical training of Manoel Augusto and his performance as pianist in Brazil and Germany. Another point investigated was the inclusion of Manuel Augusto in the musical life of Recife in several musical institutions from the 1920s in which he had a prominent role as a pioneer in conducting the promotion of culture and music education, as the Conservatório Pernambucano de Música, a Sociedade de Cultura Musical de Pernambuco and mainly in the foundation and maintenance of Pernambuco Conservatory of Music. In the last part, it investigated its pedagogical legacy through the reflections through the interviews and also the analysis of the repertoire presented by his students in auditions, recitals and concerts and also by musical reviews in newspaper articles of the period. In conclusion, we can attest that the role played by Manoel Augusto dos Santos was one of the most important to the musical culture in the city, not only because of the high artistic level reached by its numerous students who have become excellent pianists and teachers who have continued his piano school future generations, but also because of his pedagogical legacy, which has been tied deeply into the musical education of Pernambuco society over fifty years of work in the city of Recife.